Studi Eksperimen Pengaruh Penggunaan Partial Cut off blades pada Tubin Angin Tipe Savonius - Rizky Wahyu Suhadak; Saif Muizzadin Wadaullah; Donny Albari (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
The Savonius wind turbine is one of the VAWT wind turbines that easily rotates at low wind speed conditions such as in Indonesia. However, the savonius turbine has a fairly low efficiency when compared to other types of turbines. Increasing the cross-sectional area of the Savonius single stage turbine can be done by using the Partial Cut off blades model. This research was conducted to compare the performance of the Savonius turbine with Partial Cut off blades and regular blades at various wind speeds. The research was conducted experimentally in an open space at a speed of 2-6 m/s. The results of the study are shown by graphs of torque, power and efficiency to changes in wind flow speed. Application of turbine blades with Partial Cut off blades model is less effective if applied to the Savonius turbine. This is because the Partial Cut off blades have a distance between the pieces. This condition causes the freestream fluid flowing downstream to not push the turbine blades optimally. To improve the application of Partial Cut off blades in the future, it can be done by reducing the distance between the blade pieces.